History of Developmental Disability Policy in Alberta - Nilima Sonpal-Valias (The School of Public Policy Publications, 2019)
Alberta government is immersed in a full review of the Persons with Developmental Disabilities (PDD) program responsible for the delivery of services and supports to adults with developmental disabilities. With a budget of close to $1billion, PDD funds over 12,000 adults to receive home living, employment, community access and specialized services from about 160 non-profit and for-profit community disability service providers to help individuals live in their communities as inclusively and independently as possible. Despite being one of the most reviewed public programs in the province and having a series of funding increases in recent years, the program is viewed by program beneficiaries, their families, service providers and advocates as fraught with challenges. The review and the period following it during which recommendations will be made and debated provide an important window to influence policy reform.